Analisis Pengelolaan Obat Di Instalasi Farmasi Puskesmas X Kabupaten Sukoharjo - Amanta Rajendra Rafi Ramadani; Ika Purwidyaningrum; Santi Dwi Astuti (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
The management of medicines in community health centers is a key element in healthcare services. This study aims to analyze the management of medicines at the Pharmacy Installation of X Community Health Center in Sukoharjo Regency. The aim of this research is to determine the suitability of indicators for the selection, planning, procurement, distribution, and use of drugs at this community health center, and to identify the strategic position of the pharmacy installation within the SWOT matrix. This research employs a descriptive analysis study design with a nonexperimental qualitative approach. Data were collected retrospectively through a review of documented records. Data collection techniques included document review, observation, and interviews at X Community Health Center in Sukoharjo Regency. The results showed that the indicators for compliance with the community health center's formulary were in accordance with standards, but the compliance of medicine items with the national formulary and the national essential medicines list was not up to standard. In the planning and procurement stages, all indicators met standards, such as the comparison between the number of medicine items planned and those actually used, the frequency of procurement of each medicine item annually, and planning deviations. In the distribution stage, the indicators for medicine matching with stock cards and the warehouse management system met standards. In the usage stage, the percentage of prescriptions with generic medicines met standards. The SWOT analysis results indicated a position in quadrant 1.